Health care in future community: innovatively discover and respond to the needs of today’s seniors - Zhou, Bowen; Deng, Qidan; Zhou, Shiyuan; Zhuo, Dongni (Frontiers in Public Health, 2023)
In the context of the digital economy, the emergence and application of emerging technologies have accelerated the integration of traditional social structures with new technologies, leading to the inception of the "Future Community" as an innovative urban unit. With an aging population's rapid and sustained rise, integrating health and elderly care services with modern information technology is gradually moving towards holistic governance. This approach utilizes the Future Community as a medium and aims for quality enhancement and increased efficiency, which instrumentally addresses the diversified elderly care needs of China's aging era. In this study, we employed a questionnaire survey method that covered 11 communities in Tianjin City to understand better the current status and characteristics of their health and elderly care services. The survey results show that the means of community elderly care are gradually being upgraded, and the demands are shifting. Then, we arrive at three conclusions: firstly, technological innovation and smart approaches have the potential to positively influence the quality of elderly care in these communities. Secondly, allocating health and elderly care resources within communities can have a salutary effect on the psychological well-being of seniors. Thirdly, actively involving seniors in community life and governance can elevate their self-worth. At last, in conjunction with current challenges, we think that deepening multi-party collaboration, educating specialized talents, and bridging the "digital gap" would be effective ways to establish a future community for seniors.